Petre Alexandrescu, „Continentul scufundat. Conversaţii despre trecut”. Interviews by Mihaela Udrescu, preface by Cătălin Pavel. Edited by Vlad Alexandrescu. Iaşi, Bucureşti, Ed. Polirom, 2022, 463 p. - MÂRZA, Radu (Studia Universitatis Babeș-Bolyai Historia, 2023)
Memoir is an attractive literary genre (also) due to the human factor of the written text. It appeals to ordinary readers, but it also appeals to historians who are always eager to know more about the author of the memoir, their family, childhood, training, biographical and professional journeys, the people they met throughout their life, their readings and ideas, etc., all the more so when the author is also a historian.